Borders, Development, and Territory in Argentina: Indigenous Mobilization in the Central Chaco. (September 2020) - Iñigo Carrera, Valeria
One of the bases for the mobilization of indigenous peoples in Argentina in recent years has been access to, use of, and ownership of the natural resources contained in the territory they occupy or claim. Political mobilization among the Qom of Potae Napocna Navogoh in the central Chaco is a response to the modalities of intervention for development and territory configurations involved in capital accumulation that have threatened the possibility of their reproduction, and it involves conflict with both private capital and the state for territory rather than for land. Una de las bases para la movilización de los pueblos indígenas en Argentina en los últimos años ha sido el acceso, uso y propiedad de los recursos naturales contenidos en el territorio que ocupan o reclaman. La movilización política entre los Qom de Potae Napocna Navogoh en el Chaco central es una respuesta a las modalidades de intervención para el desarrollo y las configuraciones territoriales involucradas en la acumulación de capital que han amenazado la posibilidad de su reproducción, e involucra conflictos con el capital privado y el estado por el territorio antes que por la tierra.